Catmint (Nepeta nuda L.) Phylogenetics and Metabolic Responses in Variable Growth Conditions - Petrova, Detelina; Gašić, Uroš; Yocheva, Lyubomira; Hinkov, Anton; Yordanova, Zhenya; Chaneva, Ganka; Mantovska, Desislava; Paunov, Momchil; Ivanova, Lyubomira; Rogova, Mariya; Shishkova, Kalina; Todorov, Daniel; et al. (Frontiers in Plant Science, 2022)
Nepeta nuda (catmint; Lamiaceae) is a perennial medicinal plant with a wide geographic distribution in Europe and Asia. This study firstly characterized the taxonomic position of N. nuda using DNA barcoding technology. Since medicinal plants are rich in secondary metabolites contributing to their adaptive immune response, we explored the N. nuda metabolic adjustment operating under variable environments. Through comparative analysis of wild-grown and in vitro cultivated plants, we assessed the change in phenolic and iridoid compounds, and the associated immune activities. The wild-grown plants from different Bulgarian locations contained variable amounts of phenolic compounds manifested by a general increase in flowers, as compared to leaves, while a strong reduction was observed in the in vitro plants. A similar trend was noted for the antioxidant and anti-herpesvirus activity of the extracts. The antimicrobial potential, however, was very similar, regardless the growth conditions. Analysis of the N. nuda extracts led to identification of 63 compounds including phenolic acids and derivatives, flavonoids, and iridoids. Quantification of the content of 21 target compounds indicated their general reduction in the extracts from in vitro plants, and only the ferulic acid (FA) was specifically increased. Cultivation of in vitro plants under different light quality and intensity indicated that these variable light conditions altered the content of bioactive compounds, such as aesculin, FA, rosmarinic acid, cirsimaritin, naringenin, rutin, isoquercetin, epideoxyloganic acid, chlorogenic acid. Thus, this study generated novel information on the regulation of N. nuda productivity using light and other cultivation conditions, which could be exploited for biotechnological purposes.